Peranan Analisis Varians Dalam Pengendalian Dana Penanganan Fakir Miskin Dibidang Perlindungan Dan Jaminan Sosial (Studi Kasus Dinas Sosial Kabupaten Bogor) - Safira Safira; N.A. Rumiasih; Muhammad Nur Rizqi (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
Addressing poverty is a priority in social welfare development in Bogor Regency. To support this program, the government allocates funds through the Bogor Regency Social Service, particularly in the area of Social Protection and Security. However, the effectiveness of budget management is often questioned due to discrepancies between budget plans and their realization. This study aims to analyze the role of variance analysis in controlling funds for the handling of the poor in order to improve the efficiency and accountability of budget management. This study uses a qualitative approach with descriptive methods, and applies variance analysis techniques to budget and realization data at the Bogor Regency Social Service during the 2022–2024 period. Data was obtained through documentation and interviews. The results of the study show that for three consecutive years, the budget realization was always below the budget ceiling with a positive (favorable) variance, amounting to 9% (2022), 6% (2023), and 4% (2024), respectively. This difference was due to efficiency in the use of funds, not because of obstacles in program implementation. These findings indicate that variance analysis can be used as an effective control tool in identifying budget differences, evaluating fund management performance, and providing a basis for improving the planning of the following year's budget. This study also provides practical contributions to government agencies in improving the transparency and accountability of public financial management, as well as serving as a reference in the application of budget evaluation methods in the social sector.